2018
DOI: 10.1002/jcp.26862
|View full text |Cite
|
Sign up to set email alerts
|

PMLIV overexpression promotes TGF‐β‐associated epithelial–mesenchymal transition and migration in MCF‐7 cancer cells

Abstract: The epithelial-mesenchymal transition (EMT) is a key event associated with metastasis and dissemination in breast tumor pathogenesis. Promyelocytic leukemia (PML) gene produces several isoforms due to alternative splicing; however, the biological function of each specific isoform has yet to be identified. In this study, we report a previously unknown role for PMLIV, the most intensely studied nuclear isoform, in transforming growth factor-β (TGF-β) signaling-associated EMT and migration in breast cancer. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, it has been reported that cytoplasmic PML interacts with Smad‐2/3 and SARA (receptor‐activated Smad anchor), requires Smad‐2/3 to bind to SARA, and accumulate SARA and TGF‐β receptors in early endosome (Lin et al, ). More important, our recent study observed that a typical nuclear PML isoform, PMLIV promotes MCF‐7 breast cancer migration and unexpectedly facilitates TGF‐β signaling by recruitment of Smad‐2/3 into PML‐NBs and induction of Smad‐2/3 phosphorylation within a pathological setting (Y. Liu et al, ). Therefore, it can be said that PML has a close relationship with TGF‐β/Smad‐2/3 signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, it has been reported that cytoplasmic PML interacts with Smad‐2/3 and SARA (receptor‐activated Smad anchor), requires Smad‐2/3 to bind to SARA, and accumulate SARA and TGF‐β receptors in early endosome (Lin et al, ). More important, our recent study observed that a typical nuclear PML isoform, PMLIV promotes MCF‐7 breast cancer migration and unexpectedly facilitates TGF‐β signaling by recruitment of Smad‐2/3 into PML‐NBs and induction of Smad‐2/3 phosphorylation within a pathological setting (Y. Liu et al, ). Therefore, it can be said that PML has a close relationship with TGF‐β/Smad‐2/3 signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…There are six nuclear PML isoforms designated PMLI–PMLVI and one cytoplasmic isoform, PMLVIIb (Jensen, Shiels, & Freemont, ; Nisole, Maroui, Mascle, Aubry, & Chelbi‐Alix, ). The latest study of our project group found that PMLIV overexpression promotes TGF‐β‐associated epithelial–mesenchymal transition (EMT) and migration in MCF‐7 cancer cells (Y. Liu et al, ). Another study by Maroui et al () reported that PMLIII and PMLIV are key players of the interferon‐induced increase of cellular SUMOylation.…”
Section: Discussionmentioning
confidence: 99%
“…the most ability to bind to TET2 [22]. Also, PML-I and PML-IV bind to Smad2/3, but in the presence of TGF-β only PML-IV binds to phospho-Smad2/3, results in PML-IV overexpression promotes epithelial to mesenchymal (EMT) in MCF-7 tumor cells [23]. Till date, studies pertaining to PML isoform functions were focused largely on PML-IV.…”
Section: B C a Dmentioning
confidence: 99%
“…The EMT is a process involved in a pathophysiological condition in which epithelial cells acquire characteristics of mesenchymal cells [ 9 ]. EMT involves a modification of the classic epithelial phenotype and morphology to a fibroblastoid phenotype, as it favors an increase of cell migration, invasion, and resistance to anoikis and chemotherapy [ 54 , 55 ]. In the molecular context, cells undergo changes in gene expression, function, and/or activation of proteins involved in this transition [ 56 , 57 , 58 ].…”
Section: Epithelial–mesenchymal Transition (Emt)mentioning
confidence: 99%